2018
DOI: 10.1002/1873-3468.13261
|View full text |Cite
|
Sign up to set email alerts
|

Deadenylation by the CCR4‐NOT complex contributes to the turnover of hairy‐related mRNAs in the zebrafish segmentation clock

Abstract: In the zebrafish segmentation clock, hairy/enhancer of split‐related genes her1, her7, and hes6 encodes components of core oscillators. Since the expression of cyclic genes proceeds rapidly in the presomitic mesoderm (PSM), these hairy‐related mRNAs are subject to strict post‐transcriptional regulation. In this study, we demonstrate that inhibition of the CCR4‐NOT deadenylase complex lengthens poly(A) tails of hairy‐related mRNAs and increases the amount of these mRNAs, which is accompanied by defective somite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…They clearly showed that the 3′UTR of the EC gene Lfng promoted rapid mRNA decay, while the 3′UTR of fgf8 mRNA contributed to stabilization of the reporter mRNA (Hilgers et al, 2005), which is compatible with fgf8 graded expression pattern in the PSM (Dubrulle and Pourquié, 2004). Similar findings were reported for zebrafish EC genes (Fujino et al, 2018), evidencing that 3′UTR-mediated regulation of EC gene expression oscillations is a conserved feature in vertebrates. The Amacher lab went on to specify that mRNA decay of both zebrafish her1 and deltaC relies on the Pumilio response-and AU-rich-elements present in their distal 3′UTRs, in a Pnrc2-dependent manner (Gallagher et al, 2017;Tietz et al, 2020).…”
Section: Mrna Degradation Delaysupporting
confidence: 86%
See 1 more Smart Citation
“…They clearly showed that the 3′UTR of the EC gene Lfng promoted rapid mRNA decay, while the 3′UTR of fgf8 mRNA contributed to stabilization of the reporter mRNA (Hilgers et al, 2005), which is compatible with fgf8 graded expression pattern in the PSM (Dubrulle and Pourquié, 2004). Similar findings were reported for zebrafish EC genes (Fujino et al, 2018), evidencing that 3′UTR-mediated regulation of EC gene expression oscillations is a conserved feature in vertebrates. The Amacher lab went on to specify that mRNA decay of both zebrafish her1 and deltaC relies on the Pumilio response-and AU-rich-elements present in their distal 3′UTRs, in a Pnrc2-dependent manner (Gallagher et al, 2017;Tietz et al, 2020).…”
Section: Mrna Degradation Delaysupporting
confidence: 86%
“…These authors measured the lengths of the poly(A) tails of zebrafish her1, her7 and hes6, and observed that the first two genes, that display cyclic expression in the PSM, have shorter poly(A) tails, while hes6 that is expressed in a gradient has a longer one. Through the inhibition of the deadenylase complex CCR4-NOT, the authors were able to lengthen the poly(A) tails of her1 and her7, and this resulted in a 2-3-fold increase in mRNA levels, indicating an increase in mRNA stability (Fujino et al, 2018).…”
Section: Mrna Degradation Delaymentioning
confidence: 99%
“…Quantitative PCR analysis qPCR was carried out as essentially previously described (Fujino et al, 2018). Total RNA was extracted from wild-type, tbx6 ΔTR1/ΔTR1 and tbx6 −/− embryos at the 10-to 12-somite stage and subject to qPCR analysis.…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%
“…Short poly(A) tails are associated with mRNA degradation (44), and tim mRNA is thus likely unstable, as expected for a cycling transcript (14). Similarly, short half-life transcripts that encode transcription factors of the zebrafish segmentation clock display short poly(A) tails whose size is controlled by the CCR4-NOT1 complex (45). Short poly(A) tails have been recently associated with high translational efficiency (46) and the two effects of short poly(A) (instability and high translation) might be important for keeping high-amplitude tim mRNA oscillations.…”
Section: Discussionmentioning
confidence: 98%